Modified Presurgical Nasoalveolar Molding in the Infants with Complete Unilateral Cleft Lip and Palate: A Stepwise Approach - Bajaj, Ajay (Springer-Verlag, 2011)
Presurgical orthopedics in one or the other form has been an important part of the multidisciplinary approach towards the better cleft care. Presurgical nasoalveolar molding (PNAM) was described as a modified approach to the conventional form of orthopedics. PNAM not only reduces the severity of the alveolar defect before surgery, it also reduces the nasal deformity bringing it near to the normal. Nonsurgical nasal correction forms an important adjunct to the primary nasal repair at the time of primary lip repair. However, acceptance of nasoalveolar molding in Indian set-up has not been wide spread due to various reasons such as lack of the resources and inability of the parents to comply with the frequent adjustment schedule. At the Nitte Meenakshi Institute of Craniofacial surgery at the Nitte University, Mangalore, authors have developed a modification of the PNAM appliance previously described in the literature. The key modification is done at the time of fabrication of the occlusal prosthesis. This modification has made the overall procedure simpler and at the same time helped to reduce the recall visits by half of the originally required. This article describes the fabrication procedure of the modified nasal alveolar molding appliance and the modified treatment protocol in a stepwise manner.